Dairy Chemistry and Biochemistry - Fox, P. F; McSweeney, P. L. H; O'Mahony, J. A; Uniacke-Lowe, T (2015)
This book is the most comprehensive introductory text on the chemistry and biochemistry of milk. It provides a comprehensive description of the principal constituents of milk (water, lipids, proteins, lactose, salts, vitamins, indigenous enzymes) and of the chemical aspects of cheese and fermented milks and of various dairy processing operations. It also covers heat-induced changes in milk, the use of exogenous enzymes in dairy processing, principal physical properties of milk, bioactive compounds in milk and comparison of milk of different species. This book is designed to meet the needs of senior students and dairy scientists in general.
Keywords: Food -- Biotechnology; Food Science